Exploring the impact of age of onset on stereoacuity in patients with myasthenia gravis - Cheng, Chen-Yun; Chiu, Hou-Chang; Hung, Chi-Feng; Yeh, Jiann-Horng (Frontiers in Ophthalmology, 2026)
IntroductionMyasthenia gravis (MG) is an autoimmune disorder that can result in fluctuating muscle strength and various ocular manifestations. Common ocular signs and symptoms in MG patients include ptosis, limited eye movement, and diplopia.PurposeThis study aimed to investigate the association between the clinical characteristics of MG, specifically the age of onset, and stereoacuity in MG patients.DesignThis was a cross-sectional study that enrolled 150 MG patients.MethodsStereoacuity was assessed using the Butterfly Stereo Acuity Test. Main analysis was conducted using multinomial logistic regression to explore the relative risk associated with different levels of stereoacuity.ResultsThis study included 150 MG patients: 58 (38.7%) with normal stereoacuity, 80 (53.3%) with weak stereoacuity, and 12 (8%) unable to identify any stereo chart. Patients with MG onset before age 7 (n = 15) had a significantly higher risk of being unable to identify any stereo chart [relative risk ratio (RRR) = 14.73; p = 0.03]. Among ocular manifestations, ptosis (RRR = 2.33; p < 0.05) and diplopia (RRR = 2.26; p < 0.05) were associated with weak stereoacuity, whereas extraocular movement (EOM) disorder was significantly associated with being unable to identify any stereo chart (RRR = 10.57; p < 0.01).ConclusionFindings suggest that an early onset of MG may contribute to impaired stereoacuity. For patients diagnosed with MG before the age of 7, it is advisable to ensure optimal management of MG itself. Future studies should explore the potential long-term implications of early-onset MG on binocular vision, ophthalmoplegia, and the impact of ocular signs and symptoms on patients’ quality of life.